Penerapan Model Discovery Learning Pada Mata Kuliah Filsafat Ilmu - Youhanita, Ety; Eryadini, Ninies (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
Philosophy of science is a compulsory subject that must be taken as a basis for the process of developing students' self-development into moral and dignified human beings. To become people who understand philosophy, students must be active in learning they tend to be passive in the learning process. This requires lecturers to think about how to present the learning process by the characteristics of the material and students. The characteristics of students who are currently taking philosophy of science courses are known as Generation Z, where they are a generation that grew up in a technological environment that is always connected to the internet and social media. So that the learning process is more active and students are more motivated to learn, implementing the discovery learning model is the right solution. The chosen learning model is proven by a percentage of 15% of the results of classroom action research in cycle I to cycle II, where student learning activities were more active and student learning outcomes were better so that learning motivation increased and the implementation of the learning model was declared successful.